Histochemical Observations on Bursa of Fabricius of Chabro Bird - Singh, Anand (Indian Journal of Veterinary Anatomy, 2019)
The study was aimed to provide the basic findings about the histochemical details of bursa of Fabricius in Chabro birds of five different age groups (day 0, 30, 60, 90, and 150). The presence of acid, alkaline phosphatase was demonstrated in the epithelial cells lining the bursal mucosa, tunica serosa between the cortex and medulla of lymphoid follicles. Intensity of periodic acid Schiff’s (PAS) positive granules increased with the advancement of age. The cortex of bursal follicles showed intense positive reaction to alkaline phosphatase and the acid phosphatase activity increased with the advancement of age.